Commercial performance of certain introduced and indigenous clones in India - John A; Mercykutty V C; Mydin K K; Ulaganathan A (International Workshop on Rubber Tree Breeding, IRRDB, Brazil, 4-7 April 2011)
The commercial yield performance of certain introduced and indigenous clones in three large estates situated in various parts of traditional rubber growing tracts of central Kerala viz., Malankara, Koney and Chemoni estates are reported. The clones tested were RRII 5, RRII 105, RRII 203, RRII 206, RRII 208, RRII 300, RRII 308, PR 255, PR 261, GT 1, PB 260, PB 310, PB 311, PB 312, PB 314, RRIC 102, Nab 17 and SCATC -88-13. The selected clones were evaluated for yield potential, growth vigour and reaction to biotic and abiotic stresses. Tapping system followed was 1/2 Sd3. The results confirmed the superiority and suitability of clones PB 260, PB 314, PB 312, RRII 203 and RRII 105 for wide scale planting. The superiority of clones for specific traits is discussed.
Keywords: Bole volume; Growth vigour; Secondary characters; Yield